Edukasi Efek Negatif Pemaparan Media Pornografi Sebagai Strategi Pencegahan Perilaku Seksual Beresiko pada Siswa SMA di Kota Padang - Dian Paramitha Asyari; Fadhilatul Hasnah (STIKes Alifah Padang, 2023)
The development of information and communication technology on the one hand has had a positive impact on the development of people's lives. However, on the other hand, it also brings negative effects on adolescent development, especially pornography. The effects of online media have the potential to cause conflict by confirming negative stereotypes. The purpose of this PKM activity is to educate teenage students about the negative effects of watching pornographic content. This activity is carried out by providing educational socialization and informing how to block pornographic advertisements that appear on Google. The results of the activity found that as many as 96 students of public high schools and 56 students of private high schools knew the bad effects of the content. Then as many as 102 public high school students and 75 private high school students said that pornographic content advertisements often appear in the Google browser.